Sources of international family law: a posse ad esse non valet consequentia - E. P. Voytovich (Правоприменение)
The sources of international family law are not accurately defined in Russian legislation and legal doctrine, and are often misinterpreted in practice as well. The subject of this study, therefore, is the legal form of private international law norms, to determine the set of sources to be used to resolve cross-border family disputes in Russia. The research methodology adopted by the author includes the logical methods of analysis and synthesis, as well as formal, legal and comparative private scientific methods. A logical result of insufficient attention to the sources of private international law is the persisting ambiguity in their composition, which has manifested into the analysis of the sources of international family law.The author concludes that the broad understanding of private international law sources proposed by legal doctrines and the Supreme Court of the Russian Federation does not find full confirmation in resolving cross-border family disputes in practice. Outdated regulation does not allow international treaties to maintain precedence in the system of sources. Despite the Ruling of the Supreme Court of the Russian Federation on the procedure for its application, the use of international treaties has not become wide-spread in resolving cross-border family disputes by Russian courts.The inconsistency of Russian legislation with the generally recognized principles and norms of international law has sparked academic discussion regarding their regulatory impact. This, however, did not prevent the highest court from referring to them as the sources of private international law for the Russian Federation. This study demonstrates the lack of convincing evidence for their use as a source of international family law.Acts of international organizations, when provided in the form of an international treaty or regulation, can serve as a basis for resolving cross-border family disputes. Acts that do not have a similar expression are not sources, but can influence the legislator due to their rec-ommendatory nature.The domestic legislation of the Russian Federation comprises a large number of Acts con-taining the norms of international family law. While agreeing with the idea of its codification as a whole, the author opines that it requires not only a thorough analysis of de lege lata, but also a balanced approach to de lege ferenda.Customs recognized in the Russian Federation have the potential value of a source of international family law. However, at the same time, their use in resolving cross-border family disputes is not supported by empirical data.Foreign law, including foreign customs, is the set of rules that can be applied in resolving disputes, subject to regulatory permission. They should be distinguished from the sources of law of the national legal system. Therefore, it is incorrect to consider them as sources of private international law of the Russian Federation.